MANAJEMEN RANTAI PASOK BAWANG GORENG PADA INDUSTRI SAL-HAN DI KOTA PALU - Moh Rifaldi; Arifuddin Lamusa; Shintami R. Malik (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
This study aims to determine the mechanism of the fried onion supply chain in the sal-han industry in the city of palu. This research was carried out in small and medium-size industries salhan on street Sis Aljufri no. 48 Palu Cities, from March to May 2020. The respondents consisted of 10 people, namely 4 farmers, 3 traders, 1 industrial owner, and 2 consumers. Data analysis used with qualitative method analysis. The results of the analysis show that (1) The supply chain network in the Sal-Han industry is starting from farmers – collectors – industry – consumers, where each link in the chain has its own task. (2) There are3 flow patterns in the supply chain of the sal-han industry, namely the flo of products flowing from farmers to the final consumer, the flow of information flowing from two directions fromfarmers and collectors, the industry and then into the hands of consumers, financial flowsflow from consumers to industry, collectors to farmers